PERANCANGAN GAME TOP DOWN ROGUELIKE SHOOTER “ARCANA MEMORIES” PADA PC - Johny Andersen; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
This game was created using the C# programming language with the Unity Engine development program. In this game, the player will act as a young man who tries to recover his lost memories. The goal of this game is to regain the character's memory by completing tasks such as exploring the dungeon that always changes its shape, defeating all the enemies that exist, going to the last level, and defeating the final boss. The testing of this game is done by using blackbox testing method, alpha testing by supervisor, and beta testing by 37 respondents through a questionnaire. The survey shows that "Arcana Memories'' has unique and interesting gameplay with a room shuffling feature so that players can enjoy exploring dungeons that shapes and rooms are always changing.